Peer effects of working capital management: Considering the moderating effect of knowledge flow - Zhao, Mingyuan; Ming, Bingxin; Li, Yingqing; Shi, Junran (Frontiers in Psychology, 2022)
An important form of human learning and cognition is imitation. In environments where uncertainty is more incremental, imitation of peers is a natural response to uncertainty. While there are substantial literature documenting peer effects in other settings, the study of peer effects in working capital management is novel; little research exists on peer effects in working capital management and their impact mechanism. Using data of China’s listed firms from 2010 to 2021, we empirically demonstrate significant peer effects due to working capital management. Firstly, we find that the behavior of working capital management of firms in the same industry is positively related to a firm’s working capital management. We used peer firms’ target debt ratio as an instrumental variable to address potential endogeneity problem. Secondly, the moderating effects test shows that the positive relationship between the behavior of working capital management of firms in the same industry and a firm’s working capital management behavior is moderated by knowledge flow. Meanwhile, the peer effects in the high group of knowledge flow are greater than that of in the low group of knowledge flow. The study is based on the Active Intermodal Matching theory of psychology. It enriches the research findings on the moderating effect of peer effects and has important implications for policymaking to stimulate the economy.